Increasing Students' English Vocabulary Mastery Through Guess Card Games: Vocabulary - Bawuno, Gabriella Mercy; Rombepajung, Paula; Olii, Sanerita T. (Program Studi Pendidikan Bahasa Inggris, 2024)
This research is based on the problem that students face in English learning, which is the lack of vocabulary. The lack of vocabulary mastery makes some students hard to understand the material and also hard to express their ideas in English. This research aims to see whether Guess Card Games increase students’ English vocabulary mastery. This research took place at SMP Negeri 2 Tondano. The subjects of the study in this research were 20 students of class VIIIB SMP Negeri 2 Tondano. The research design applied was pre-experimental research design with one group pre-test and post-test. The instrument used was a test in the form of multiple-choice questions. There was a significant difference between the results of the pre-test and post-test. The mean score of the pre-test was 57,2 and in the post-test 71,3. It was confirmed that Guess Card Games have a significant effect on increasing students’ English vocabulary mastery.